Nurturing a Generation Excelling in Faith and Intellect: Reconstructing the Islamic Education Curriculum in Boarding Schools - Fitri Ali Masnur; Muhammad Iqbal; Tiy Kusmarrabbi Karo; Fakhrurrozi; Zulham Effendi (ASSUNNAH PRESS, 2024)
This research aims to evaluate the effectiveness of the reconstruction of the Islamic Education Curriculum (PAI) at SMP-IT Al-Fauzan Bangkinang in enhancing students' understanding and competence in religious studies, as well as its impact on the formation of students' character and morals. The significance of this research lies in the context of a boarding school, which has a greater potential to shape students' character and morals. The research methodology employed is a case study with a qualitative approach, utilizing observations, in-depth interviews, and document analysis related to the PAI curriculum. The findings reveal that the reconstruction of the PAI curriculum has a positive impact on students' understanding and competence in religious studies, such as mastering materials on the Quran, hadith, aqidah, ibadah, and akhlak. Additionally, religious extracurricular activities such as Hifzul Qur'an, Syahril and Fahmil Qur'an, and Hifzul Hadis have significantly contributed to the formation of students' character and morals in accordance with Islamic teachings. This research concludes that the reconstruction of the PAI curriculum at SMP-IT Al-Fauzan Bangkinang, supported by a diverse range of extracurricular programs, has successfully fostered a generation of young Muslims who excel academically and possess noble character.